Preliminary Remarks on Particles' Contextuality. Erroneous Thoughts on Submerging Particles in a Cotext - Kisiel, Anna (Lingua Posnaniensis, 2012)
The article is dedicated to contextuality of particles in Polish language. The author calls for a understanding contextuality as a language unit's requirement of a directly preceeding text having its own TRS, which is somehow connected with elements of TRS introduced by the language unit. Generally speaking, the connection consists in coforming the two subordinate structures into one TRS in a frame of superordinate theme. Erroneous thoughts on contextuality of particles are shown by presenting three language units seen by some linguists as contextual, namely tylko ‘only’, też ‘also’ and wręcz ‘simply’. The author points out that contextuality, which is regarded as a matter of their meaning is in fact a consequence of their usage.